Growth, structural, thermal and optical properties of Mg2+ -Co2+ doped potassium acid phthalate crystals - Hossain, Mostak; Begum, Shahan Ara; Podder, Jiban (Journal of Bangladesh Academy of Sciences, 2014)
Single crystals of pure potassium acid phthalate (KAP) and magnesium-cobalt (Mg2+-Co2+) co-doped potassium acid phthalate crystals were grown by an isothermal evaporation method. Optically transparent and coloured KAP single crystals were grown by doping divalent bimetallic impurities. Enhancement of the metastable zonewidth was achieved by the addition of co-doped bimetallic impurities in KAP solution. It is anticipated that these larger cations play a vital role in the growth mechanism and it favours to reduce the formation of secondary nucleation by positioning the doped metal ions into the interstitial sites. The XRD results confirm that the incorporation of bimetallic ions into the KAP crystal lattice. The optical transmission is found to decrease in Mg-Co doped crystals compared to that of pure KAP. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17557 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 165-172, 2013